Analysis of sound field in dominicans’ church in Cracow - Plewa, Magdalena (Archives of Acoustics, 2007)
This publication presents the results of sound field analysis: simulation using ray method, finite element model below 200 Hz and real reverberation time measurements in band 125–8000 Hz, executed in Dominicans’ church in Cracow. Effects of calculations and measurements show that big part of energy is accumulated in low frequencies what causes significant influence of this band on the acoustics of analyzed interior. Results of ray-method simulation and MLS measurements allowed to receive the values of reverberation time in octave bands. Big architectonical dimensions caused difficulties in sound field analyzing but designers of basilica achieved magnificent acoustic effect without present theoretical knowledge. This article, using computer-aided methods, analyzes results of their work.